2021
DOI: 10.1111/1750-3841.15586
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and plasma carotenoids are positively associated with alpha diversity in the fecal microbiota of pregnant women

Abstract: Because microbes use carotenoids as an antioxidant for protection, dietary carotenoids could be associated with gut microbiota composition. We aimed to determine associations among reported carotenoid intake, plasma carotenoid concentrations, and fecal bacterial communities in pregnant women. Pregnant women (n = 27) were enrolled in a two‐arm study designed to assess feasibility of biospecimen collection and delivery of a practical nutrition intervention. Plasma and fecal samples were collected and women were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 74 publications
2
17
0
Order By: Relevance
“…Another recent small-scale cross-sectional study showed that dietary and plasma carotenoids were positively associated with alpha diversity in the fecal microbiota of pregnant women ( n = 27). In particular, correlations with α and ß-carotene were found [ 54 ]. The effects of carotenoid supplementation on gut composition are few, and a recent review tried to summarize the main findings by concluding that the “carotenoids–gut” interaction still represents a fundamental research question that must be addressed [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another recent small-scale cross-sectional study showed that dietary and plasma carotenoids were positively associated with alpha diversity in the fecal microbiota of pregnant women ( n = 27). In particular, correlations with α and ß-carotene were found [ 54 ]. The effects of carotenoid supplementation on gut composition are few, and a recent review tried to summarize the main findings by concluding that the “carotenoids–gut” interaction still represents a fundamental research question that must be addressed [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its neurological harm may outweigh bene ts from reduced caloric intake. Conversely, rich contents of vitamins [37][38][39] , minerals 40 , carotenoids [41][42][43] , and avornoids 44 in NSJ may have advantaged the effects of excessive sugar and thus protected brain health.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, its neurological harm may outweigh bene ts from reduced caloric intake. Conversely, rich contents of vitamins [37][38][39], minerals [40], carotenoids [41][42][43], and avonoids [44] in NSJ may have advantaged the effects of excessive sugar and thus protected brain health. Furthermore, oxidative damage caused by the β-amyloid peptide in the pathogenesis of dementia may be hydrogen peroxide mediated [45].…”
Section: Discussionmentioning
confidence: 99%